Final answer:
To solve the expression 8 4/5 + (3 2/10 - 1 1/5), we simplify the mixed numbers and then perform the operations to get the final result of 10.8.
Step-by-step explanation:
To solve the expression 8 4/5 + (3 2/10 - 1 1/5), we need to simplify each of the mixed numbers first.
8 4/5 = 8 + 4/5 = 8 + 0.8 = 8.8
3 2/10 = 3 + 2/10 = 3 + 0.2 = 3.2
1 1/5 = 1 + 1/5 = 1 + 0.2 = 1.2
Now, we can substitute these values back into the original expression and simplify:
8.8 + (3.2 - 1.2) = 8.8 + 2 = 10.8
Therefore, the expression is equivalent to 10.8.